Penilaian Jurnal internasional : An Analysis on the Impact of Participatory Budgeting and Procedural Fairness Toward Manager's Commitment and Performance - Astuty, Widia (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Penilaian Jurnal internasional : An Analysis on the Impact of Participatory Budgeting and Procedural Fairness Toward Manager's Commitment and Performance